Analisis Kinerja Industri Minyak Kelapa Sawit di Indonesia Menggunakan Paradigma Structure Conduct Performance : Studi Kasus Pada 10 Perusahaan Minyak Kelapa Sawit - Kifli Rifki Mubarok, Mohammad; Susanto, Joko; Bhinadi, Ardito (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
This study aims to analyze the performance of the palm oil industry in Indonesia, using the Structure Conduct Performance (SCP) paradigm. The data in this study uses secondary data namely the annual reports of 10 companies engaged in the palm oil industry in Indonesia from 2015 to 2020 which are published on the company’s website. The data is then processed using Microsoft Excel 2016 software to obtain data on Market Share, Concentration Ratio 4, Minimum Efficiency of Scale, Capital Labor Ratio, Internal Efficiency, and Price Cost Margin. The analysis method of this research uses panel data regression analysis. The results of this study indicate that Concentration Ratio 4 has a negative and significant effect on Price Cost Pargin, while Capital Labor Ratio and Internal Efficiency have a positive and significant impact on Price Cost Margin of thePalm Oil Industry in Indonesia in 2015 – 2020.